"Flood Area Mapping by Using Computed River Overflow." - Irfan Kusnandi, author 1 (2013)
HATHI The 4th International Seminar 2013. International Seminar on "Water Related Disaster Solutions". Yogyakarta, 6-8 September 2013; ISBN: 978-979-988-5-5-0